Comparison of microstructure, second phases and texture formation during melt processing of Bi-2212 mono- and multifilament wires. (19th August 2016) - Kadar, J; Scheuerlein, C; Rikel, M O; Di Michiel, M; Huang, Y
Abstract: Based on simultaneous in situ high energy synchrotron micro-tomography and x-ray diffraction (XRD) measurements we compare the microstructural changes and the formation of second phases and texture during the processing of Bi-2212 round wires with 15 μ m filament diameter (multifilament) and 650 μ m filament diameter (monofilament) fabricated using identical Bi-2212 precursor. The monofilament tomograms show in unprecedented detail how the distributed porosity agglomerates well before Bi-2212 melting decomposition to form lenticular voids that completely interrupt the filament connectivity along the wire axis. When the Bi-2212 phase completely melts connectivity in the axial wire direction is established via the changes in the void morphology from the lenticular voids to bubbles that remain when Bi-2212 crystallises out of the melt. By measuring the attenuation of the monochromatic x-ray beam, the associated Bi-2212 mass density changes have been monitored during the entire heat cycle. The XRD results reveal that the wire architecture can have a strong influence on the phase evolution during the melt processing heat treatment affecting the reversibility of Bi-2212 melting decomposition reaction. A strong Bi-2212 texturing is only achieved in the multifilament wire, while in the monofilament wire Bi-2212 crystallites grow with nearly random orientation.